Analysis of Avtur/Jet A-1 stock resilience at XYZ Company - Setiaji, Efraim Dandy Pandawa; Pratama, Ibnu Lukman (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
AY Airport is an international airport that continues to operate every day. The need for aviation fuel or Avtur is always needed and not in small quantities. The condition of the Covid-19 pandemic, which requires X Company to meet fuel needs regardless of the circumstances, is a challenge for X Company. With current conditions that are always changing, an analysis of stock resilience was carried out at the Avtur storage tank facility in 2018-2022 to identify the coverage of days that Y Depot the regulations issued by BPH Migas and Pertamina Aviation. The results stated that stock resilience was at a good level during the pandemic with resilience above 9 days, and some stocks were declared critical in the pre-pandemic period.